Combined Functional and Structural Imaging of White Matter Reveals Brain Connectivity Alterations in Fibromyalgia Patients - Gao Z; Xie X; Liu F; Xu T; Zhang N; Zhang X; Li Y; Kong Y; Lv D; Wu T (Journal of Pain Research)
Ziyi Gao,1 Xinyan Xie,1 Fuyuan Liu,2 Tong Xu,1 Nan Zhang,1 Xinran Zhang,1 Yun Li,1 Youyong Kong,2 Dongling Lv,3 Ting Wu1 1Department of Radiology, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 2Jiangsu Provincial Joint Inter-School of Computer Science and Engineering, Southeast University, Nanjing, People’s Republic of China; 3Department of Cardiology, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of ChinaCorrespondence: Ting Wu, Email fsyy00598@njucm.edu.cn Dongling Lv, Email lvdongling1226@163.comBackground: Fibromyalgia syndrome (FMS) is a prevalent central chronic pain condition of unknown pathophysiology. White matter (WM) plays a crucial role in brain signal transmission, and WM structural abnormalities have been reported in FMS. However, functional WM changes in FMS patients have not been investigated. This study aimed to investigate whether functional neural changes in WM accompany structural changes observed in FMS.Methods: The study included 43 FMS patients and 43 healthy controls. Structural and functional analyses of WM were assessed using fractional anisotropy (FA) and amplitude of low-frequency fluctuation (ALFF), respectively, to explore WM alterations in FMS patients.Results: Structural analysis revealed altered FA values in the left corticospinal tract (CST), right cingulate/hippocampus, right fornix/stria terminalis (FX/ST), superior occipitofrontal fasciculus (SOFF), right superior corona radiata (SCR), right posterior corona radiata (PCR), sagittal stratum, and left medial lemniscus (ML) in FMS patients. Some regions showing structural changes also showed changes in resting-state functional activation. Functional analysis showed that FMS patients have reduced ALFF values in the left CST, left ML, right PCR, right cingulate/hippocampus, and right FX/ST. Furthermore, the degree of ALFF reduction in the right cingulate/hippocampus and left ML was positively correlated with anxiety, depression, and pain severity scores.Conclusion: This study provides a preliminary exploration of the mechanisms underlying FMS in terms of WM functional signals. The observed reduction in WM functional activation offers novel insights into the pathophysiology of FMS and highlights potential targets for WM-focused therapeutic strategies.Keywords: brain function, brain structure, fibromyalgia, white matter, ALFF